The Performance of REDD+: From Global Governance to Local Practices - Arts, B.; Ingram, V.J.; Brockhaus, Maria (MDPI, 2019)
Whilst ‘REDD’ is the acronym for reducing emissions from deforestation and forest degradation, ‘REDD+’ refers to efforts to reduce emissions from deforestation and forest degradation, foster conservation, promote the sustainable management of forests, and enhance forest carbon stocks [...]